Forensic toxicology of benzodiazepines: neuropharmacological effects, analytical challenges, and emerging detection strategies - Irfan Thalib, Husna; Damanhory, Ahmed Abdelghany; Hanin Shaikh, Ayesha; Haidar, Shyma; Khan, Sariya; Jamal, Ayesha; Abdelghany, Omar Ahmed (Frontiers in Toxicology, 2025)
The increasing misuse of benzodiazepines (BZDs) in drug-facilitated crimes (DFCs) has become a serious concern for forensic experts, healthcare professionals, and legal authorities. These drugs, which are commonly prescribed for anxiety and sleep disorders, are also used to commit crimes such as sexual assault and robbery. Their sedative and memory-blocking effects render them particularly dangerous. One of the biggest challenges is that BZDs are rapidly broken down in the body, limiting the time available for detection. This creates major problems in forensic investigations and reduces the chance of holding offenders accountable for their actions. In addition, memory loss caused by BZDs often affects a victim’s ability to recall events, making legal cases more challenging. This review aims to comprehensively synthesize the current knowledge on the use of BZDs in DFCs, their neuropharmacological mechanisms, and the challenges associated with their detection. It also discusses legal issues and emerging forensic tools that may help overcome the current limitations. By addressing this issue from medical, forensic, and legal perspectives, this review aims to recommend better prevention strategies, more effective investigations, and stronger legal outcomes for cases involving benzodiazepine-facilitated crimes.